THE EFFECT OF WORK STRESS TO EMPLOYEE PERFORMANCE AT BANK RAKYAT INDONESIA IN MANADO BRANCH - Paputungan, Fitryah (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
ABSTRACT Stress is a common element in any kind of job and people face it in almost every walk of life. In the banking sector particularly, higher management do not realize the impact of stress on employee performance which ultimately results in critical managerial dilemmas. Work overload & time pressure to complete too much work in short span of time is big source of stress which decrease the performance of employees. The purpose of this research are to analyze the influence of work stress on employee performance at Bank Rakyat Indonesia in Manado Branch, North Sulawesi and to identify the most significant variable of work stress that influence employee performance. Work stress and employee performance are the supporting theories for this research.Â  The population are all employees and customers of BRI Manado Branch with sample consists of 100 respondents are determined. Results and conclusions show that work stress significantly affects employee performance and communication has the most significant influence to employee performance. Keywords: work stress, employee performance